Understanding the Public Health Implications of Prisoner Reentry in California State-of-the-State Report - Davis, Lois M. (RAND Corporation, 2011)
Examines the health care needs of newly released California prisoners; the communities most affected by reentry and the health care safety net of those communities; the critical roles that health care providers, other social services, and family members play in successful reentry; and the effects of reentry on the children and families of incarcerated individuals. Recommends how to improve access for this population in the current fiscal environment.